Large-area transparent flexible guanidinium incorporated MAPbI3 microstructures for high-performance photodetectors with enhanced stability. Issue 4 (21st January 2020) - Kumar, Gundam Sandeep; Sarkar, Piyush Kanti; Pradhan, Bapi; Hossain, Mozakkar; Rao, K. D. M.; Acharya, Somobrata
Abstract : Random percolative microstructures of mixed cation perovskites lead to ambient stable transparent and flexible photodetectors with enriched photoresponse. Abstract : Unveiling the transparency and flexibility in perovskite-based photodetectors with superior photoresponse and environmental stability remains an open challenge. Here we report on guanidinium incorporated metal halide perovskite (MA1− x Gua x PbI3, x = 0 to 0.65) random percolative microstructure (RPM) fabrication using an ultra-fast spray coating technique. Remarkably, RPMs over a large area of 5 × 5 cm 2 on flexible substrates with a transparency of ∼50% can be achieved with enriched environmental stability. Transparent photodetectors based on MA1− x Gua x PbI3 ( x = 0.12) RPMs manifest excellent performance with a responsivity of 187 A W −1, a detectivity of 2.23 × 10 12 Jones and an external quantum efficiency of 44 115%. Additionally, the photodetectors exhibited superior mechanical flexibility under a wide range of bending angles and large number of binding cycles. Integrating features including transparency, high performance, stability, flexibility and scalability within a photodetector is unmatched and holds potential for novel applications in transparent and wearable optoelectronic devices.